Conservação in situ de Maytenus ilicifolia Mart. ex Reiss. (Celastraceae) na Floresta Nacional de Irati - PR - Mazza, Maria Cristina Medeiros (Universidade Federal de São Carlos, 2006)
The conservation of biodiversity is a priority and strategic question at world level. During the last decades, the intensive extraction of non-timber species resulted in the loose of biological diversity and degradation of natural forests. The recent expansion of medicinal plants, almost exclusively founded on extractivism contributes to degradation of these species in their natural environment. Maytenus ilicifolia Mart. ex Reiss. ( espinheira-santa ), species from the Sub-Tropical Forests, mainly from the Mixed Ombrophylous Forest (Araucaria Forest), has medicinal properties for treatment of gastrointestinal diseases. It is now listed among the endangered species of the flora of Parana and São Paulo States, in the categories of rare and almost extinct respectively, and has been considered as having priority for protection and sustainable use. The Protected Areas play a fundamental role in the in situ conservation of the biological diversity; however, the composition and importance of the biodiversity distributed in these Areas are not yet well known. There is neither report about in situ conservation of medicinal species in Brazil nor studies about their ecology in the Protected Areas. This study evaluates the phenology, size structure and population dynamics of Maytenus ilicifolia in the Irati National Forest, in order to have basis for its in situ conservation. The Irati National Forest (25°21 S e 50°35 W), a Protected Area of sustainable use, is localized in the municipalities of Fernandes Pinheiro and Teixeira Soares, Parana State. The phenologic study of this species was done in 78 adult individuals, during two years. The intensity of flowering and fructification events were estimated using a scale from zero to four, with 25% in every class. For population size structure, height and diameter were evaluated in five groups of Maytenus ilicifolia between 2004 and 2006, using the Gini coefficient. The dynamics was evaluated using transition matrices for five developmental stages. It was used to estimate the finite growth rate of the population (λ), the stable structure and the reproductive value during ...
Keywords: Ecologia de populações; Conservação (Biologia); Espécies em extinção; Plantas medicinais; Dinâmica de populações; CIENCIAS BIOLOGICAS::ECOLOGIA